Early intervention, treatment and rehabilitation of employees with common mental disorders by using psychotherapeutic consultation at work: study protocol of a randomised controlled multicentre trial (friaa project) - Weber, Jeannette; Angerer, Peter; Brenner, Lorena; Brezinski, Jolanda; Chrysanthou, Sophia; Erim, Yesim; Feißt, Manuel; Hansmann, Marieke; Hondong, Sinja; Kessemeier, Franziska Maria; Kilian, Reinhold; Klose, Christina; et al. (BMC public health, 2021)
Common mental disorders are one of the leading causes for sickness absence and early retirement due to reduced health. Furthermore, a treatment gap for common mental disorders has been described worldwide. Within this study, psychotherapeutic consultation at work defined as a tailored, module-based and work-related psychotherapeutic intervention will be applied to improve mental health care.